LAMP3 expression in the liver is involved in T cell activation and adaptive immune regulation in hepatitis B virus infection - Wang, Zilong; Wang, Xiaoxiao; Jin, Rui; Liu, Feng; Rao, Huiying; Wei, Lai; Chen, Hongsong; Feng, Bo (Frontiers in Immunology, 2023)
Background: The disease burden caused by chronic hepatitis B virus (HBV) infection is still heavy, and the current treatment scheme was unable to achieve a complete cure. Chronic HBV infection is usually accompanied by changes in natural and adaptive immunity. As a marker expressed on dendritic cells (DCs), whether LAMP3 participates in chronic HBV infection deserves further analysis. Methods: we retrieved transcriptional information of chronic HBV infection from the GEO databases. The LAMP3 expression in the liver of chronic hepatitis B (CHB) patients was analyzed in 3 GEO datasets and confirmed in our own validation cohort (27 CHB patients). Differentially expressed genes (DEGs) were obtained from one chronic hepatitis B (CHB) cohort by the comparison of LAMP3high and LAMP3low expression subgroups. Those genes were under GO, KEGG and GSEA enrichment analyses to decipher the influence of LAMP3 on the biological process and immunity changes in HBV infection. Furthermore, we investigated the potential relations between LAMP3 levels and the abundance of infiltrating immune cells and liver dysfunction. Results: Compared with healthy controls, LAMP3 expression upregulated in transcriptional profiles of liver from CHB patients. The high LAMP3 expression was related to T cell activation and chemokine signaling pathway. The LMAP3 gene was positively linked to marker sets of infiltrating activated Treg cells, T cell exhaustion, monocytes and DCs. Moreover, CHB patients with high LAMP3 expression have unfavorable liver dysfunction. Conclusions: LAMP3 was a gene related to HBV infection, which might involve in the occurrence of HBV infection by regulating T cell activation and adaptive immune response.